2020
DOI: 10.1177/1559325820914184
|View full text |Cite
|
Sign up to set email alerts
|

Blood Gene Expression Profile Study Revealed the Activation of Apoptosis and p53 Signaling Pathway May Be the Potential Molecular Mechanisms of Ionizing Radiation Damage and Radiation-Induced Bystander Effects

Abstract: Radiotherapy is an effective treatment for local solid tumors, but the mechanism of damage to human body caused by radiation therapy needs further study. In this study, gene expression profiles of human peripheral blood samples exposed to different doses and rates of ionizing radiation (IR) were used for bioinformatics analysis to investigate the mechanism of IR damage and radiation-induced bystander effect (RIBE). Differentially expressed genes analysis, weighted gene correlation network analysis, functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…However, the sensitivity of spermatogenic populations to RIAEs is unclear. Previous studies have demonstrated that RIAEs can initiate apoptosis in distant tissues ( Koturbash et al, 2008 ; He et al, 2020 ). In addition, Zhang et al reported that fractionated irradiation (X-ray, 8Gy×3 d) of the right thorax damaged the ultrastructure of the BTB and increased apoptotic spermatogonia cells, which located at the outermost layer of the seminiferous epithelium of the testis ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the sensitivity of spermatogenic populations to RIAEs is unclear. Previous studies have demonstrated that RIAEs can initiate apoptosis in distant tissues ( Koturbash et al, 2008 ; He et al, 2020 ). In addition, Zhang et al reported that fractionated irradiation (X-ray, 8Gy×3 d) of the right thorax damaged the ultrastructure of the BTB and increased apoptotic spermatogonia cells, which located at the outermost layer of the seminiferous epithelium of the testis ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of testicular cell apoptosis directly induced by ionising radiation is mostly mediated by a p53-dependent Bax-caspase-3-mediated pathway ( Shahin et al, 2018 ; He et al, 2020 ). Since the testes of mice in the C-irradiation group are not directly exposed to ionising radiation, we speculate that the mechanism of testicular cell apoptosis induced by C-irradiation is different from that induced by direct radiation.…”
Section: Discussionmentioning
confidence: 99%
“…While RT is known to affect the tumor microenvironment, including tumor blood vessels and immune system cells ( 16 19 ), how it triggers systemic bystander effects is unclear. Previous studies have implicated apoptosis and p53 signaling in such effects ( 20 ). Through preliminary analysis of single-cell data, we provide evidence that the immune microenvironment of tumors varies during irradiation, and that radiation-specific CD8+ T cells may be the primary risk factor for RT-associated adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, their concentrations in the creeping wood sorrel were low (see below). Second, lauric acid is known to be contained in mulberry leaves [93,94]. However, because lauric acid is volatile, it may be minimized during an autoclave sterilization process of Silk Mate L4M.…”
Section: Artificial Diet Preparationmentioning
confidence: 99%